Relationship between cultural intelligence and career and work adaptability in nursing students - Sevinc, Sibel; Ozdemir, Serap (Journal of the Pakistan Medical Association, 2024)
Objective: To investigate the relationship between cultural intelligence and career and work adaptability among nursing students. Method: The descriptive, cross-sectional study was conducted at Kilis 7 Aralik University Nursing Department in Turkey from April to May 2019, and comprised nursing students of either gender. Data was gathered using Cultural Intelligence Scale and Career and Work Adaptability Questionnaire. Data was analysed using SPSS24. Results: Of the 277 subjects, 162(58.5percent) were females and 115(41.5percent) were males. The overall mean age was 21.21±1.81 years. The mean Cultural Intelligence Scale score was 95.17±18.16. The mean Career and Work Adaptability Questionnaire score was 115.69±19.38. There was a positive correlation between the total scores and subscale scores of both the scales (r=598, p 0.001). The student’s father’s occupation, desire to work overseas, feeling like a good fit for nursing, and feeling prepared for professional life significantly affected cultural intelligence (p 0.05). The student’s father’s occupation significantly affected career and work adaptability (p=0.001). Conclusions: There was a positive correlation between the total scores and subscale scores of Cultural Intelligence Scale and Career and Work Adaptability Questionnaire. Key Words: Culture, Intelligence, Career, Work adaptability, Nursing student.